Discriminate and indiscriminate use of amoxicillin antibiotic and detection of its residue in poultry edible tissue by thin layer chromatography (TLC) method - Islam, Md Shakil; Islam, Md Zahorul; Islam, Md Shafiqul (Asian-Australasian Journal of Food Safety and Security, 2019)
Antibiotic residue is a burning question in the present world. Antibiotic remain in edible tissues of poultry as a residue due to indiscriminate use in the veterinary field. Human health is at risk of antibiotics due to poultry edible tissues. In this study, we used broiler chicks as a laboratory animal to investigate the judicial use of amoxicillin antibiotic for human health concern. Chicks were reared accordingly and on day 14 the chicks were randomly divided into three groups (n=6) namely control (group A), discriminate (group B) and indiscriminate (group C). At the age of day 16, amoxicillin treatment was started and continued for seven days for discriminate group (Group B) and 15 days for indiscriminate group. In case of discriminate group, seven days withdrawal period was properly maintained, whereas, no withdrawal period was maintained in case of indiscriminate group. In control group, no positive samples were detected by thin layer chromatography (TLC) analysis, whereas, the amoxicillin intensity in liver, kidney, thigh muscle and breast muscle were positive by TLC as 57.82%, 52.30%, 45.18% and 49.96% respectively for indiscriminate group. Similarly 46.81% liver, 44.65% kidney, 29.27% thigh muscle and 32.73% breast muscle were the amoxicillin intensity in discriminate group. The level of amoxicillin were found significantly different between control & discriminate, control & indiscriminate and discriminate & indiscriminate groups by TLC analysis. Therefore, amoxicillin residue present in both discriminate and indiscriminate group but the intensity percentage (%) was highest in case of indiscriminate group indicates high residual concentration. Asian Australas. J. Food Saf. Secur. 2019, 3(2), 96-102